THE INFLUENCE OF CULTURAL PRACTICE ON POPULATION OF PEA LEAFMINER (Liriomyza huidobrensis) AND ITS PARASITOIDS IN POTATO - Suryawan, Ida Bagus Gde; Reyes, Stephen G. (Indonesian Agency for Agricultural Research and Development - MOA, 2006)
Pea leafminer (Liriomyza huidobrensis) is the major pest of potato crop in Indonesia. The use of insecticides to control the pest is ineffective and harmful to the natural enemies. The study aimed to find out a promising cultural practice for leafminer management on potato crop. The study was conducted at a farmerâs field in Bali in 2004. Potato plants (Granola variety) were grown in a raised-bed plot of 10 m x 1 m. The treatments evaluated were standard cultural practice (C), C plus reflective plastic mulch (RPM) (CM), farmerâs practice (F), vermicompost (V), and V plus RPM (VM). All treatments were arranged in RCBD with five replications. From each plot, 10 plant samples were randomly taken to observe the presence of larvae, mines, and adults. Larvae and adults of leafminer andmines were separately counted from the top, middle, and bottom parts of the plant samples. Parasitoids were collected from the infested leaves of the plant samples. Emerged parasitoids were counted and put into vials with 70% ethyl alcohol and then identified. The results showed that the population of adults, larvae of L. huidobrensis, and mines were less in C, CM, V, and VM treatments compared to farmers practice (F). However,RPM (CM and VM) treatments significantly reduced population of leafminer and mines. The highest population of adults, larvae, and mines on RPM treatment were less than 1.5, 8.5, and 10 per plant, respectivelyÂ compared to other treatments which were greater than 3.2 for adults, 12.4 for larvae, and 12.7 for mines. Parasitoid population and parasitism level were more in vermicompost treatments (V and VM) compared to othertreatments (C, CM, and F). The results showed that application of pesticides was ineffective against leafminer and reduced parasitoid population; in the other hand RPM was effective to control leafminer although the effect on parasitoids was not clear. Parasitoid species that were found associated with potato crop were Hemiptarsenus varicornis, Neochrysocharis sp., and Opius sp. Combination of RPM with standard practice and vermicompost are prospective for leafminer management in potato crop, however, VM is friendlier to environment regarding sustainableagriculture.